2012
DOI: 10.1002/bit.24710
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐heparin polyelectrolyte multilayers on cortical bone: Periosteum‐mimetic, cytophilic, antibacterial coatings

Abstract: Cortical bone allografts suffer from high rates of failure due to poor integration with host tissue, leading to non-union, fracture, and infection following secondary procedures. Here, we report a method for modifying the surfaces of cortical bone with coatings that have biological functions that may help overcome these challenges. These chitosan-heparin coatings promote mesenchymal stem cell attachment and have significant antibacterial activity against both S. aureus and E. coli. Furthermore, their chemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…The GAGs found in proteoglycans are polyanions and can therefore be assembled into controlled nanostructures such polyelectrolyte multilayer coatings (PEMs) and GAGrich polyelectrolyte complex nanoparticles (PCNs) by electrostatic complexation with polycations. [ 34,[45][46][47][48][49][50][51][52][53][54][55] We have demonstrated that PCNs and graft copolymers may mimic the size, composition, and growth factor stabilization and delivery properties of proteoglycans found in native ECM. [ 31,56 ] Other groups have also demonstrated growth factor delivery using GAG-based PCNs.…”
Section: Nanostructured Gag-based Tissue Scaffolds For Growth Factor mentioning
confidence: 99%
“…The GAGs found in proteoglycans are polyanions and can therefore be assembled into controlled nanostructures such polyelectrolyte multilayer coatings (PEMs) and GAGrich polyelectrolyte complex nanoparticles (PCNs) by electrostatic complexation with polycations. [ 34,[45][46][47][48][49][50][51][52][53][54][55] We have demonstrated that PCNs and graft copolymers may mimic the size, composition, and growth factor stabilization and delivery properties of proteoglycans found in native ECM. [ 31,56 ] Other groups have also demonstrated growth factor delivery using GAG-based PCNs.…”
Section: Nanostructured Gag-based Tissue Scaffolds For Growth Factor mentioning
confidence: 99%
“…Previously, our group has demonstrated that heparin‐chitosan complexes and coatings on tissue culture polystyrene, glass, and titanium can bind, stabilize, and deliver FGF‐2 . We further developed similar nanostructured coatings for cortical bone, demonstrating support for mesenchymal stem cell adhesion, antimicrobial properties, cell proliferation, and sustaining ASCs in an osteoprogenitor phenotype . Thus, we hypothesize that a polysaccharide‐based tissue engineered periosteum composed of heparin‐coated chitosan nanofibers would (1) provide sustained delivery of heparin‐binding growth factors FGF‐2 and TGF‐β1, (2) support ASC delivery, and (3) improve allograft incorporation in a critical‐sized mouse femoral defect.…”
Section: Introductionmentioning
confidence: 96%
“…Proposed tissue engineered periosteums include those composed of synthetic polymers, ceramics, and natural proteinaceous materials . However, few attempts have been made to create a tissue engineered periosteum from purely polysaccharide materials incorporating glycosaminoglycans (GAGs), which are key functional components of the natural periosteum …”
Section: Introductionmentioning
confidence: 99%
“…The CT backbone consists of randomly repeating units of glucosamine and N-acetylglucosamine, whereby the former (i) mediate the solubility of CT in aqueous systems [1]; (ii) are amenable to chemical functionalisation towards the synthesis of water-soluble CT derivatives [2]; and (iii) provide CT with unique antibacterial properties [3]. With the breakout of antibiotic resistance, CT has found wide applications as haemostat [4], wound dressing [5] and antibacterial coating [6], in the form of electrospun webs [7], nano-particulates [8] or water-swollen networks [9].…”
Section: Introductionmentioning
confidence: 99%